Social Class and Criminality among Young People: A Study Considering The Effects of School Achievement as a Mediating Factor on the Basis of Swedish Register and Self-Report Data - Ring, Jonas (Journal of Scandinavian studies in criminology and crime prevention, 2007)
This study focuses on the associations between parental social class, school achievement, and criminality among young people. The study hypothesizes that there is a relationship between class background and school achievement, and between school achievement and crime, and examines whether school achievement is a mediating variable between class background and crime. The study builds on analyses of both register and self-report data. The register study includes all the members of a Swedish birth cohort and utilizes measures of social class, school achievement (at grade 9 compulsory school), and offending (at age 15-22) contained in official registers. The self-report study is based on a large sample of adolescents in grade 9 (aged 15) and utilizes self-report measures. The results show that there is a weak but statistically significant relationship between social class background and criminality in both data sets, indicating that working-class background is associated with a higher risk for offending. The article concludes that social class background seems to have some effect on criminality among young people but that this effect is mediated by school achievement. This mediating effect is evident in both the register and self-report material and for both males and females. By contrast, the effects on crime of the structural background factors of coming from a broken home or an immigrant background are not mediated by school achievement